Effect of extrusion and compression moulding on the thermal properties of nylon-6/silica aerogel composites. (July 2018) - Krishnaswamy, Suryanarayanan; Tinsley, Lawrence; Marchante, Veronica; Addepalli, Sri; Huang, Zhaorong; Abhyankar, Hrushikesh
The article presents the effect of a lower extrusion speed and compression moulding processes on the thermal properties of polyamide 6 (PA-6)/aerogel composite. Scanning electron and optical microscope images showed that although most of the aerogel was destroyed during extrusion at 65 r/min, extrusion at 5 r/min showed a better retention of the aerogel structure. However, when subjected to moulding in a compression press, both composites extruded at different speeds suffered significant damage. Nevertheless, the extruded samples did show a lower thermal conductivity compared to the virgin polymer. Further, it was observed that the sample extruded at 5 r/min had a lower damage coefficient value with an overall loss of around 33% to the aerogel structure when compared to the material extruded at 65 r/min, which endured a structural loss of 41% to the aerogel in it.